The cooperation between business organizations, trade unions, and the state during the COVID‐19 pandemic: A comparative analysis of the nature of the tripartite relationship. Issue 2 (14th December 2021) - Brandl, Bernd
Abstract: The COVID‐19 outbreak has led to an increase in social dialogue in general and, in particular, to an increase in tripartite cooperation between social partners' organizations and state authorities. This paper takes a critical look behind this cooperation and investigates the underlying rationales behind the tripartite cooperation in 19 countries. It is shown that even though the cooperation generally fulfilled its problem‐solving function, an expressive function that signaled unity was identified to be of equal importance in such a time of crisis. This expressive function is also identified to potentially serve as the basis for a renewed social partnership.